Periodicals Received (Review of Economic Studies, 1940)
Journal Article Periodicals Received Get access The Review of Economic Studies, Volume 7, Issue 2, February 1940, Page 138, https://doi.org/10.1093/restud/7.2.138-a Published: 01 February 1940